Model-based Instruction as an Activity in Teaching a Pharmaceutics Course - Almukainzi, May (Indian Journal of Pharmaceutical Education and Research, 2021)
Objectives: Pharmaceutics is the core component of pharmacy education; the course helps pharmacy students to understand the influence of drugs' physicochemical characteristics and manufacturing parameters on therapeutic performance. Although they are important, pharmaceutics concepts can be "dry," especially since many pharmacy schools teach pharmaceutics using the traditional lecture-only format. Therefore, activities through which students can perceive the relevance of the subject to clinical applications and that keep learners engaged in their classes are very much in demand. Methods: In this study, the incorporation of model-based instruction (MBI) in teaching a pharmaceutics course was explored, and the reasons for integrating this type of model were discussed. We presented a case study involving students transferring scientific knowledge to tactile models. The students' perception of the usefulness of this activity was evaluated. Results: The open-ended questions in the survey showed that the models helped learners to understand the content and enjoy the class. Conclusion: The study provided examples of interactive, simple, easy, and inexpensive MBI, where students could demonstrate their content understanding and their skills. The process of creating and evaluating models transforms the student class experience from static to dynamic and may help students achieve profound and long-lasting learning.
Keywords: Simulation and education; Modelling and education; Physical models and teaching; Small-group activities; PharmD; Pharmacy education